2021
DOI: 10.1186/s12872-021-02450-3
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial injury in hospitalized COVID-19 patients: a retrospective study, systematic review, and meta-analysis

Abstract: Introduction The majority of studies evaluating the effect of myocardial injury on the survival of COVID-19 patients have been performed outside of the United States (U.S.). These studies have often utilized definitions of myocardial injury that are not guideline-based and thus, not applicable to the U.S. patient population. Methods The current study is a two-part investigation of the effect of myocardial injury on the clinical outcome of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 25 publications
2
18
0
2
Order By: Relevance
“…In a systematic review and meta‐analysis, Changal et al 10 showed that hospitalized COVID‐19 patients have a high prevalence of myocardial injury, which was associated with a high risk of mortality. The studies included in this meta‐analysis were primarily conducted during the active phase of COVID‐19.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a systematic review and meta‐analysis, Changal et al 10 showed that hospitalized COVID‐19 patients have a high prevalence of myocardial injury, which was associated with a high risk of mortality. The studies included in this meta‐analysis were primarily conducted during the active phase of COVID‐19.…”
Section: Introductionmentioning
confidence: 99%
“…7 In addition to potential injury associated with the illness, some medications used to treat patients with COVID-19 8 and drug interactions may also have potential side effects specific to the heart. 9 In a systematic review and meta-analysis, Changal et al 10 showed that hospitalized COVID-19 patients have a high prevalence of myocardial injury, which was associated with a high risk of mortality. The studies included in this meta-analysis were primarily conducted during the active phase of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Myocardial injury appears to be linked to severity of COVID-19 disease and mortality [ 4 10 ]. Mortality from COVID-19 is reported to be higher among hospitalized patients with myocardial injury, compared to those without, [ 4 , 6 , 7 , 11 , 12 ]. Indicating that myocardial injury may portend a poorer prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies (46 studies) reported the impact of CI on mortality (Table 1) [5,12,15,17,18,20,[22][23][24]29,[31][32][33]35,39,40,[42][43][44][45][46][47][48][49][50][51][52][53][56][57][58][59][60][61][62][63][64][65][66][67]70,73,74,[76][77][78].…”
Section: Resultsmentioning
confidence: 99%
“…Among the different statistical indices, OR was the most frequently used (29 studies) [4,5,12,21,22,[24][25][26][27][32][33][34]40,[42][43][44]47,48,50,52,58,59,[62][63][64]70,74,77,78], while RR and HR were used in 10 [15,18,23,39,45,48,56,57,72,73] and 6 studies [51,52,60,65,66,77], respectively. A minority of meta-analyses investigated pooled differences of cardiac biomarkers between severe vs non-severe disease or survivors vs non survivors (Table 1).…”
Section: Resultsmentioning
confidence: 99%